Analysis of Revenue Diversification and Its Impact on ROA: Study on State-Owned Banks 2018-2024 - Handriyani Dwilita; Neng Sri Wardhani; Syafira Salsabiela (Harmoni Economics: International Journal of Economics and Accounting, 2025)
The financial crisis has prompted global banks to strategize, reduce loans between countries to the emergence of regional banks that fill the gap, and the emergence of regional and global competition between banks. Competition and digital transformation encourage Indonesian banks to grow and develop. One of them is the determination of bank revenue strategies to support banking performance, especially state-owned banks. The theory of income diversification in several countries, both neighboring countries, and Europe considers whether or not to diversify its income composition strategy.  This study aims to examine the composition of state-owned bank revenues for the period 2018 to 2024. Is there income diversification? And how does it impact on the value of ROA of state-owned banks. This research is a qualitative research with a descriptive approach, with a research sample of 4 state-owned banks. So the research is called case study research with saturated samples. The results of the study revealed that state-owned banks (BRI, BNI, Mandiri, and BTN) did not diversify their revenues, banks only focused on interest income which controlled almost 90% of bank revenue. There was an increase in the portion of interest income in the 4th period, but it did not have an impact on the increase in ROA. Therefore, the income strategy by focusing on 1 main type of income, namely interest income, does not have an impact on the increase or decrease in the value of ROA.